Isolation and identification of Aeromonas salmonicida of bovine origin and its genome-wide and pathogenicity analysis - Wang, Qian; Dong, Xiaoping; Cui, Miaomiao; Liang, Xuechao; Sun, Yiya; Chen, Shulin; Feng, Shuo; Zheng, Xiwen; Liu, Yingzi (Frontiers in Microbiology, 2026)
Aeromonas salmonicida subsp. pectinolytica is a type of bacterium capable of growing at 37 °C, and it was traditionally considered non-pathogenic. In this study, a bacterial strain designated JMAV14 was isolated from the liver tissue of a diseased and deceased bovine in Chaoyang City, Liaoning Province, China. Phylogenetic analysis based on core genome single-copy orthologous genes and whole-genome SNP loci, combined with average nucleotide identity (ANI) analysis, identified JMAV14 at the species level of Aeromonas salmonicida. Further bacteriological identification methods, including VapA gene detection and physiological and biochemical characteristic tests, ultimately classified it as an atypical bovine-derived Aeromonas salmonicida subsp. pectinolytica strain. Pathogenicity assays showed that this strain caused a mortality rate of 70% in mice with a median lethal dose (LD₅₀) of 1.330 × 107 CFU per mouse, and a mortality rate of 50% in crucian carp (Carassius carassius). These results indicate that JMAV14 possesses strong pathogenicity and broad cross-species infection ability, which challenges the traditional understanding that this subspecies is non-pathogenic. This study clarifies the biological characteristics of bovine-derived Aeromonas salmonicida subsp. pectinolytica during cross-species infection, providing a theoretical basis for the establishment of identification methods, diagnostic techniques, and prevention and control strategies for this bacterium.